Dreams and realities in the local governance of Hungary - PÁLNÉ KOVÁCS, Ilona (Discussion Papers, 2011)
The aim of this paper is to introduce the development process of the local governance system in Hungary, highlighting the paradox of the starting model selection and the real state of the art of local governments in Hungary. This paradox is not the special case of Hungary since the framework type of regulation always bears the risk that “life” overwrites the legal dreams. The speciality of the transitional countries is that we did have normative ideas about the western type of governance, but without having a real picture on how to implement and use the fashionable institutions and norms in our contexts. The legislator at that time expected that the declaration of autonomy and democracy will lead to a completely new quality of local governmental performance both in terms of public services and local democracy. From the distance of 20 years, we shall realise that the legal model on its own was unable to guarantee the autonomy and efficiency of local governments. The processes occurring in the local governance system of Hungary produced adequate evidence for the evaluation of the real space of “Europeanisation” and also for forecasting the near future of decentralisation in the new member states, where the polarisation and fragmentation is a possible argumentation in the hands of national governments explaining their centralising ambitions.